2014
DOI: 10.1007/s10584-014-1121-4
|View full text |Cite
|
Sign up to set email alerts
|

Long-term variability of sea surface temperature in Taiwan Strait

Abstract: Long-term variability of sea surface temperature

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 44 publications
2
18
0
Order By: Relevance
“…In Bohai Sea, northern China, a shallow semi-enclosed sea, the sea surface temperature increased at a rate of 0.011˚C y −1 from 1960 to 1997 [21]. In the Taiwan Strait, the SST increased by 1.0˚C (at a rate of 0.045˚C y −1 ) from 1976 to 1998, and the long-term net warming increased three-fold from the South China Sea to the East China Sea [22]. An early study on the Sea Surface Temperature (SST) in Daya Bay shows an increase rate of 0.11˚C y −1 during 1970-2005 based on in situ data [15].…”
Section: Increase Of Water Temperature In the Daya Baymentioning
confidence: 99%
“…In Bohai Sea, northern China, a shallow semi-enclosed sea, the sea surface temperature increased at a rate of 0.011˚C y −1 from 1960 to 1997 [21]. In the Taiwan Strait, the SST increased by 1.0˚C (at a rate of 0.045˚C y −1 ) from 1976 to 1998, and the long-term net warming increased three-fold from the South China Sea to the East China Sea [22]. An early study on the Sea Surface Temperature (SST) in Daya Bay shows an increase rate of 0.11˚C y −1 during 1970-2005 based on in situ data [15].…”
Section: Increase Of Water Temperature In the Daya Baymentioning
confidence: 99%
“…Variation in squid cohorts can be utilized as an indicator of the effects of El Niño-Southern Oscillation events on ecosystems and productivity according to their remarkable metabolism and physiological characteristics. Furthermore, the climatic effects as well as increases in SST associated with global warming are other significant factors that influence the marine ecosystem in the SECS (Belkin and Lee 2014;Lan et al 2014). The annual landings of swordtip squid decreased from 21,000 metric tons in 2005 to 3,000 metric tons after 2011 in the coastal fisheries of Taiwan, and the area of the fishing grounds has been shrinking (Zhang et al 2012;Wang et al 2013).…”
mentioning
confidence: 99%
“…The warming rate was considerably greater than that in the SCS and Kuroshio region off Eastern Taiwan. Belkin and Lee (2014) observed that the SST gradient between the CCC and offshore TS waters abruptly decreased in 1992 and remained low through 2011. The MK trend detection method indicated that during 1992 -1994, the SST in the TS (except in the KB region) showed an abrupt increase in the SST.…”
Section: Discussionmentioning
confidence: 98%
“…Long-term SST warming in the TS was discussed by Belkin and Lee (2014). They used the climatological data set HadISST1 (spatial resolution: 1° × 1°; total number of grids in the TS: 17) from the UK Met Office Hadley Centre for the period between 1957 and 2011 and showed that SST warming in the TS was considerably enhanced in winter.…”
Section: Discussionmentioning
confidence: 99%